Examining the impact of chronic diseases on activities of daily living of middle-aged and older adults aged 45 years and above in China: a nationally representative cohort study - Zhonghua Ai; Churou Tang; Xuan Wen; Karthikesu Kartheepan; Karthikesu Kartheepan; Songyuan Tang (Frontiers Media S.A., 2024)
BackgroundChina has by far one of the fastest-aging populations in the world. Increasing age is often accompanied by an increasing prevalence of chronic diseases and impaired Activities of Daily Living (ADL). The aim of this study was to analyze the effects of chronic diseases on ADL in Chinese middle-aged and older adults and to provide a scientific basis for delaying the impairment of ADL and prolonging the self-care life expectancy of middle-aged and older adults.MethodsThis investigation utilized the survey information of 10,096 middle-aged and older adults from the China Health and Aging Tracking Survey (CHARLS) of 2011 as baseline data, then followed up this cohort until 2018, and performed multifactorial analyses using Cox proportional risk models to explore the strength of the associations between chronic diseases and the risk of impaired ADL in middle-aged and older adults.ResultsAmong the middle-aged and older adult population, the presence of hypertension was associated with a 38% higher risk of impaired ADL compared to those without the condition (HR = 1.38,95% CI:1.24-1.54); the involvement of heart disease was associated with a 27% higher risk of impaired ADL compared to those without the condition (HR = 1.27,95% CI:1.10- 1.46); the existence of arthritis was associated with a 38% higher risk of impaired ADL in middle-aged and older adults compared to those without arthritis (HR = 1.38,95% CI:1.25-2.08); additionally, the risk of impaired ADL with one or ≥ 2 chronic diseases was increased by 34% (HR = 1.34, 95% CI:1.18-1.52) and 84% (HR = 1.84, 95% CI:1.63-2.08) in middle-aged and older adult individuals, respectively.ConclusionHypertension is a risk factor for impaired ADL at any age in the subjects of this study. Examining the association between the number of chronic diseases and impairment in activities of daily living, it was revealed that the risk of ADL impairment increased with the number of chronic diseases in both the middle-aged (45-59 years) and older adult (60-74 years) groups.